Desain Booth Tahu Jemprit Surakarta Sebagai Inovasi Media Promosi - Saputro, Adhi; Henny Lukitasari, Evelyne; Wibowo, Yudi (Universitas Sahid Surakarta, 2023)
Booth is a mini stage inside which is used as an arena for product or service exhibitions. Booths are usually used by companies to display the products that the company sells. Booths in the current era are not only used by companies in exhibitions but also used in selling products directly to consumers. Seeing how important the booth's role is besides being a place to sell as well as promotion development, Tahu Jeprit needs it. The purpose of this design is to create an attractive booth concept in accordance with the vision and image of Tahu Jemprit to increase the interest of potential consumers of Tahu Jemprit Surakarta. The design method used in this design is qualitative by collecting data at the location and interviewing the Tahu Jemprit outlet owner. The result of this design is a booth that is used as a place to sell and also as a promotional media development, in addition to media plans in the form of t-shirts, aprons, posters, menu lists, aprons, food packaging, and x banners. Keywords : Booth, Tofu, Design, Food,